Comprehensive analysis of constitutional mismatch repair deficiency-associated non-Hodgkin lymphomas in a global cohort - Rigaud, Charlotte; Forster, Victoria J; Al-Tarrah, Hiba; Attarbaschi, Andishe; Bianchi, Vanessa; Burke, Amos; Burkhardt, Birgit; Colas, Chrystelle; Devalck, Christine; Edwards, Melissa; Elitzur, Sarah; Garthe, Anne-Kathrin; et al. (Pediatric blood & cancer, 2024)
BACKGROUND: Constitutional mismatch repair deficiency syndrome (CMMRD) is a rare childhood cancer predisposition syndrome associated with a broad spectrum of malignancies, including non-Hodgkin lymphomas (NHL). Most patients die due to cancer before the age of 20 years. Limited data exist on CMMRD-associated lymphomas and their outcome. METHODS: We conducted a retrospective study including all CMMRD-associated NHL patients registered before 2020 in the European and North American databases or reported by members of the European Intergroup for Childhood Non-Hodgkin Lymphoma (EICNHL). Events considered to define event-free survival included relapse/progression, second malignancy (SML), or death, whichever occurred first. FINDINGS: The analysis included 74 patients, with 20 having multiple metachronous NHL. The median age at diagnosis was 9.4 years. Previous malignancies were reported in 36% of the patients, café au lait spots in 96%, and consanguinity in 54%. The initial lymphoma subtypes were 53 T-cell lymphoblastic lymphomas (T-LBL), four B-lymphoblastic lymphomas, and 17 mature B-cell non-Hodgkin lymphoma (B-NHL). All patients were treated with curative intent, with current chemotherapy regimens adapted to their subtype. The median follow-up was 8.7 years. After the first lymphoma, the 5-year event-free and overall survival rates were, respectively, 23.5% [95% confidence interval (CI): 14.9-35.1] and 61.5% [95% CI: 49.6-72.1]. The 5-year cumulative risk of progression/relapse, SML or death as a first event was 20.8%, 52.9%, and 2.7%. INTERPRETATION: Standard treatments for sporadic NHL are effective in most CMMRD-associated NHL cases, but multiple malignancies, including lymphomas, impair prognosis. Future strategies should evaluate the potential of less genotoxic therapies, including immunotherapy, in preventing SMLs while maintaining effective control of NHL.
Keywords: dospělí; kolorektální nádory; Neoplastic Syndromes, Hereditary; Female; Infant; dítě; předškolní dítě; dědičné nádorové syndromy; Adult; mladý dospělý; ženské pohlaví; lymphoblastic lymphomas; CMMRD; Colorectal Neoplasms; Adolescent; nádory mozku; lidé; second malignancy; následné studie; míra přežití; prognóza; lymphomas; retrospektivní studie; nehodgkinský lymfom; Male; Follow-Up Studies; Lymphoma, Non-Hodgkin; kojenec; Child, Preschool; Young Adult; Brain Neoplasms; Prognosis; Survival Rate; genetic predisposition; Child; mužské pohlaví; Retrospective Studies; mladiství; Humans